2017
DOI: 10.1111/jan.13264
|View full text |Cite
|
Sign up to set email alerts
|

Support workers in community mental health teams for older people: roles, boundaries, supervision and training

Abstract: Local and national attention is needed to prevent 'drift' into activities that both support workers and registered practitioners consider outside their remit. Barriers to training and further qualification need to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 32 publications
(35 reference statements)
0
52
0
Order By: Relevance
“…Support workers contribute to the care of people with severe and enduring mental health problems in the community . Within CMHTs for older people, it has been reported that they undertook diverse roles and our data confirmed this . However, in memory clinics, they were reported as having a more specific role — the provision of support and education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support workers contribute to the care of people with severe and enduring mental health problems in the community . Within CMHTs for older people, it has been reported that they undertook diverse roles and our data confirmed this . However, in memory clinics, they were reported as having a more specific role — the provision of support and education.…”
Section: Discussionmentioning
confidence: 99%
“…22 Within CMHTs for older people, it has been reported that they undertook diverse roles and our data confirmed this. 23 However, in memory clinics, they were reported as having a more specific role-the provision of support and education. Other research has suggested that the workload of a social worker in a CMHT is contingent on the structure of the team.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most striking change was in the number of teams containing assistant‐grade support workers (87.0%), considering that just 4 years previously, a quarter of teams had no access to them at all. Recent qualitative work has shed light on the wide variety of tasks that support workers undertake in CMHTs, and the supervisory and training challenges this brings . Nevertheless, still less than a third of CMHTs had all 6 key disciplines as core team members; almost a third had no core team social workers; and a tenth could not access any psychology input.…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative work has shed light on the wide variety of tasks that support workers undertake in CMHTs, and the supervisory and training challenges this brings. 31 Nevertheless, still less than a third of CMHTs had all 6 key disciplines as core team members; almost a third had no core team social workers; and a tenth could not access any psychology input. Further, the findings reflect a global trend in healthcare provision towards an increase in the proportion of unqualified as opposed to qualified staff, [32][33][34] and a relative increase in the presence of nonmedical as opposed to medically trained personnel.…”
Section: Team Structure and Compositionmentioning
confidence: 99%
“…In the first place, there is a high variability of educational levels, inadequate training according to the workplace demands and the educational interventions carried out have been ad-hoc (Karacsony, Chang, Johnson, Good, & Edenborough, 2018). The fact that many of them work without being trained (Craftman, Grundberg, & Westerboth, 2019) is often due to workplace conditions such as low wages and time pressure (Wilberforce et al, 2017;Estabrooks, Squires, Carleton, Cummings, & Norton, 2015), as well as the lack of standardized training programs that give access to such jobs, as it occurs with unregulated care providers in Canada (Kelly, & Bourgeault, 2015). And in the second place, they suffer from burnout.…”
Section: Training Programs For Caregiversmentioning
confidence: 99%